DEVELOPMENT AND SCIENTIFIC JUSTIFICATION OF THE DESIGN OF ORTHOPEDICAL FOOTWEAR FOR PATIENTS WITH INJURIES TO THE SOUL-FOOT JOINT - Мuhammedova Madina (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article discusses modifications made to the State Standard 3927-88 footwear template for creating orthopedic footwear for patients with ankle joint injuries. Based on these modifications, an orthopedic footwear design was developed and scientifically substantiated. A special shape was given to the sole of the footwear. The article presents a scheme for assembling the upper part based on the developed orthopedic footwear design, as well as a scheme for assembling the entire footwear.